On the Use of Humour in Counseling - Klein, Joel P. (Canadian Journal of Counselling and Psychotherapy, 2012)
The techniques of famous comic playwrights are explicated in an attempt to establish prominent parallelisms between the literary and therapeutic use of humour. On the first level of comparison, the sources of human belief in what is true and real are explained. It is shown that they rest on certain subjective but rarely questioned assumptions about human nature. Using the well developed literary devices as a model for illustrating the manifold ways in which reality can be interpreted, the essay then proceeds to elaborate on ways in which the counselor can profitably employ similar strategies with his clients. On a deeper level of comparison, it is suggested that the miniature world of the theatre and the phenomenological universe of the client both emerge from an arbitrary verbal syntax which circumscribes the number and nature of the possible alternative explanations of reality. The author's own assumption about truth is that by using the model as a form of intellectual inquiry, the results of psychological investigation can be confirmed and advanced by external disciplines.